Diversity and community structure of rapids-dwelling fishes of the Xingu River: Implications for conservation amid large-scale hydroelectric development. (June 2018) - Fitzgerald, Daniel B.; Sabaj Perez, Mark H.; Sousa, Leandro M.; Gonçalves, Alany P.; Rapp Py-Daniel, Lucia; Lujan, Nathan K.; Zuanon, Jansen; Winemiller, Kirk O.; Lundberg, John G.
Abstract: A recent boom in hydroelectric development in the world's most diverse tropical river basins is currently threatening aquatic biodiversity on an unprecedented scale. Among the most controversial of these projects is the Belo Monte Hydroelectric Complex (BMHC) on the Xingu River, the Amazon's largest clear-water tributary. The design of the BMHC creates three distinctly altered segments: a flooded section upstream of the main dam, a middle section between the dam and the main powerhouse that will be dewatered, and a downstream section subject to flow alteration from powerhouse discharge. This region of the Xingu is notable for an extensive series of rapids known as the Volta Grande that hosts exceptional levels of endemic aquatic biodiversity; yet, patterns of temporal and spatial variation in community composition within this highly threatened habitat are not well documented. We surveyed fish assemblages within rapids in the three segments impacted by the BMHC prior to hydrologic alteration, and tested for differences in assemblage structure between segments and seasons. Fish species richness varied only slightly between segments, but there were significant differences in assemblage structure between segments and seasons. Most of the species thought to be highly dependent on rapids habitat, including several species listed as threatened in Brazil, were either restricted to or much more abundant within the upstream and middle segments. Our analysis identified the middle section of the Volta Grande as critically important for the conservation of this diverse, endemic fish fauna. Additional research is urgently needed to determine dam operations that may optimize energy production with an environmental flow regime that conserves the river's unique habitat and biodiversity. Highlights: 193 rapids-dwelling fish species were sampled prior to flow alteration. Fish community structure differed significantly between river segments. Rapids specialists and threatened species were concentrated in the Volta Grande. The Volta Grande rapids are now flooded and dewatered due to a hydropower facility. Maintaining rapids in the dewatered section will be critical for aquatic diversity.